Correction: Model molecules to classify CH⋯O hydrogen-bonds. Issue 58 (5th July 2018) - Vibhute, Amol M.; Priyakumar, U. Deva; Ravi, Arthi; Sureshan, Kana M.
Abstract : Correction for 'Model molecules to classify CH⋯O hydrogen-bonds' by Amol M. Vibhute et al., Chem. Commun., 2018, 54, 4629–4632.